MiT family translocation renal cell carcinoma with retroperitoneal metastasis in childhood: a case report - Yang, Kaihang; Ma, Yuhao; Dai, Shuyang; Dong, Rui (Frontiers in Pediatrics, 2023)
RCC accounts for only 0.1%-0.3% of all kidney tumors and 2%-6% of malignant kidney tumors in children. Accounting for approximately one-third of the total number of cases in children and adolescents with RCC, Xp11 tRCC is the most common subtype of the MiT family translocation renal cell carcinoma, which is a group of rare childhood and adult tumors, characterized by recurrent gene rearrangements of TFE3. The Xp11 tRCC. Here we report a relatively rare case of a 6-year-old male patient with MiT family translocation renal cell carcinoma (MiTF tRCC), which developed retroperitoneal metastasis. The patient underwent partial nephrectomy, nephropathy resection, abdominal lymph node resection, and intestinal adhesion lysis. Microscopically, we detected focal and nest clump-shaped clusters of tumor cells whose cytoplasm was bright and clear. Immunohistochemistry showed tumor cells diffusely expressed TFE3, and fluorescence in situ hybridization (FISH) demonstrated disruption of the TFE3 locus, confirming the diagnosis of Xp11 tRCC, the most common subtype of MiTF tRCC. Eventually, the patient obtained good therapeutic results. This case can provide a good reference and guidance for pediatric urologists and oncologists to recognize and diagnose rare renal cell carcinoma in children.